PENGARUH LITERASI KEUANGAN, TEKNOLOGI DIGITAL TERHADAP KINERJA UMKM KECAMATAN SEPULU - Anwaruddin, Anwaruddin; Tarman, Manah (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine how financial literacy and digital technology impact the business performance of MSMEs in Sepulu District, Bangkalan Regency. This study is based on the fact that MSMEs still lack understanding financial literacy and use of digital technology, which impacts suboptimal business performance. This study was conducted using a quantitative explanatory research approach. This study involved all MSMEs in the culinary sector in Sepulu District, Bangkalan Regency, consisting of 372 business units, and 93 respondents selected through purposive random sampling technique. Data collection was carried out using a Likert-scale questionnaire, after which the data were processed through multiple linear regression analysis with the assistance of the SPSS program. The results showed that financial literacy partially had no effect on MSME performance, while digital technology had a positive and significant effect on MSME business performance. Simultaneously, financial literacy and digital technology significantly influenced MSME business performance.